2008
DOI: 10.4012/dmj.27.392
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength Comparison and Scanning Electron Microscopic Evaluation of Three Orthodontic Bonding Systems

Abstract: This study sought to assess the efficacy of two self-etching primer systems (Transbond Plus and Beauty Ortho Bond) on orthodontic brackets. Therefore, shear bond strengths and bracket-adhesive failure modes (ARI scores) were determined and compared against an etch-and-rinse adhesive system (Transbond XT) under two experimental conditions (dry and saliva application). Shear bond strength test was performed at a crosshead speed of 0.5 mm/min, while enamel surfaces and enamel-adhesive interfaces were examined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…Numerous studies have investigated the strength of self-etching primer systems 15,18,19,[23][24][25][26][27][28][29][30][31][32][33] . Most of these studies demonstrated that self-etching systems have significantly lower SBS values than conventional acidetching systems 18,24,26,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the strength of self-etching primer systems 15,18,19,[23][24][25][26][27][28][29][30][31][32][33] . Most of these studies demonstrated that self-etching systems have significantly lower SBS values than conventional acidetching systems 18,24,26,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that bond strength values of between approximately 6.0 and 8.0 MPa are sufficient for clinically effective orthodontic bonding 12,13) . Self-etching primer systems for use in orthodontics have been studied and the shear bond strength values were similar to those with a conventional etch & rinse system 3,7,9) . On the other hand, bond failure of brackets not only can be frustrating for the practitioner, but also can significantly affect treatment efficiency and have an economic impact on a practice 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Excess bonding material was removed with a small scaler. All samples were light-cured for 9 . Table 1 Materials and instruction employed in present study 20 seconds (10 seconds from each proximal side).…”
Section: Preparation For Shear Bond Strength Testmentioning
confidence: 99%
See 2 more Smart Citations